uORF-mediated translational regulation of PERK: implications for cell homeostasis and human disease - Fernandes, Rafael (2020)
Tese de doutoramento em Biologia (Biologia de Sistemas), apresentada à Faculdade de Ciências da Universidade de Lisboa, 2020.